Decision of decentralization in a healthcare service–a case of diabetes management - Mishra V.; Samuel C.; Sharma S.K. (My University, 2025)
Healthcare services face a dual challenge of being accessible as well as affordable. Making health centres available at remote locations increases the accessibility of the service but results in low utilization of resources, which eventually results in higher cost of service. This study proposes a middle-path approach in which some components of services are available at the central facility only, while the others are available at central as well as remote locations. The study proposes and uses a Multi-Attribute Utility Theory (MAUT) approach to determine which component should be kept at the central facility. To elaborate the method, a case study approach using a diabetes management as a case organization was used. Taking a utility score of 0.5 as the cut-off point, the study concludes that Hospitalization, Neuropathy detection, Pathology, and Medicine (Pharmacy) should be kept at the central facility only. The study is first of its kind and provides an objective approach for decentralization in the case of healthcare services using the utility of the service components for a policy-maker as the criteria of selection. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.